Prevalence Of Hypertension in Gujarati School Going Children and Adolescents in Anand District - Verma , Vivek; Singh, S K (National Journal of Community Medicine, 2012)
Background: Childhood hypertension is now days becoming big problem worldwide. Gujarati school age children are not much studied regarding cardiovascular risk factors like hypertension; especially in the central Gujarat, no such study has been reported so far. Therefore, we conducted this study to assess prevalence of hypertension and relationship of blood pressure with body mass index and body surface area in Gujarati school going children and adolescents in Anand district of Gujarat. Methodology: A cross-sectional study of 1087 Gujarati school going children and adolescents of 5-18 years was conducted between 2008 and 2010 in Anand district of Gujarat to get a distribution profile of blood pressure, BMI and BSA (body surface area). Results: The overall prevalence of prehypertension was 10.8% (6.16% for SBP and 5.61% for DBP) and that for hypertension was 9.2% (5.06% for SBP and 5.09% for DBP). In boys, overall prevalence of prehypertension and hypertension were 9.63% (4.82% for SBP and 6.15% for DBP) and 9.8% (6.31% for SBP and 5.65% for DBP) respectively and, that was 9.07% (4.54% for SBP and 4.95% for DBP) and 10.31% (5.77% for SBP and 6.19% for DBP) in girls. The blood pressure was positively correlated with age, height, BMI and BSA. Conclusion: The high prevalences of prehypertension and hypertension in Gujarati children and adolescents obtained in this study indicate the need for regular evaluation of cardiovascular status in Indian school children.